HIV-AIDS prevention in the conception of HIV-positive young people - Stella Regina Taquette; Luciana Maria Borges da Matta Souza
ABSTRACT OBJECTIVE To analyze the conception of seropositive young people on how to prevent HIV infection. METHODS This is a qualitative study using semi-structured interviews with HIV-positive young people whose diagnosis was made in adolescence 5 years ago or less. We followed a semi-structured script containing sociodemographic data and an open question on HIV/AIDS prevention. The interviews were recorded and fully transcribed, then analyzed with the support of the webQDA software. We used the categories that compose the concept of vulnerability as a theoretical basis for data analysis. RESULTS We interviewed 39 young people, 23 girls and 16 boys. Some perceive the prevention of HIV infection only as an individual issue, summarizing it to the use of condoms and self-care. Most of the interlocutors point out educational strategies as the most relevant for prevention but used in a permanent and non-punctual way. In schools, they believe it is necessary to include younger students and their family. Guidelines should be given by people who can use the language of young people and preferably by HIV-positive people, to show the reality of those who have AIDS. In the programmatic field, they suggest intensifying campaigns in the media, distributing condoms in large scale, producing vaccines and medicines that cure. No one mentioned the female condom, the rapid test, nor the availability of sexual and reproductive health care. CONCLUSIONS The qualification and expansion of communication strategies on sexuality in schools is urgent and essential in HIV and AIDS prevention in adolescence, contrary to the current trend of restricting the discussion of these topics in education policies.